2021
DOI: 10.1007/s13202-021-01407-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of asphaltene stability predicting models in field environment and development of new stability predicting model (ANJIS)

Abstract: Asphaltene Precipitation is a major issue in both upstream and downstream sectors of the Petroleum Industry. This problem could occur at different locations of the hydrocarbon production system i.e., in the reservoir, wellbore, flowlines network, separation and refining facilities, and during transportation process. Asphaltene precipitation begins due to certain factors which include variation in crude oil composition, changes in pressure and temperature, and electrokinetic effects. Asphaltene deposition may o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The colloidal instability index formula CII is used to calculate the stability of asphaltene in crude oil in the bulk phase. If CII > 0.9 asphaltene is unstable in crude oil, CII < 0.7 asphaltene is stable, and 0.9 < CII < 0.7 asphaltene stability is uncertain . The CII formula is given below. normalC normalI normalI = normalS + normalA normals normalR + normalA normalr where S, As, R, and Ar are saturates, asphaltenes, resin, and aromatics in weight percentage (wt %) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The colloidal instability index formula CII is used to calculate the stability of asphaltene in crude oil in the bulk phase. If CII > 0.9 asphaltene is unstable in crude oil, CII < 0.7 asphaltene is stable, and 0.9 < CII < 0.7 asphaltene stability is uncertain . The CII formula is given below. normalC normalI normalI = normalS + normalA normals normalR + normalA normalr where S, As, R, and Ar are saturates, asphaltenes, resin, and aromatics in weight percentage (wt %) .…”
Section: Resultsmentioning
confidence: 99%
“…If CII > 0.9 asphaltene is unstable in crude oil, CII < 0.7 asphaltene is stable, and 0.9 < CII < 0.7 asphaltene stability is uncertain. 86 The CII formula is given below.…”
Section: Model Oils (Acidic and Basic)mentioning
confidence: 99%
“…This can explain why light crude oils are reported by some authors to be more prone to cause asphaltene precipitations than heavy oils [14][15][16][17]. Apart from the abovementioned methods, various predictive models and experimental techniques have been implemented to estimate oil stability throughout the years, such as the colloidal instability index (CII) [18][19][20][21], colloidal stability index (CSI) [19,21,22], stability index (SI) [19,22,23], Stankiewicz plot (SP) [19,21,24], qualitativequantitative analysis (QQA) [21], stability cross plot (SCP) [21,25], Heithaus parameter (or parameter P) [26], heptane dilution (HD) [27,28], toluene equivalence (TE) [3,29,30], spot test [26,[31][32][33][34][35] and separability number (SN) [26,36,37], Jamaluddin method (JM) [38][39][40], modified Jamaluddin method (MJM) [41], density-based asphaltene stability envelope (DBASE) [19], in-line filtration method [42], 1D low-field nuclear magnetic resonance relaxometry and chemometric methods [43,…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 22 Different models like the colloidal instability index (CII), stability index (SI), colloidal stability index (CSI), Stankiewicz plot (SP), ANJIS Model, qualitative–quantitative analysis (QQA), and stability cross plot (SCP) were developed and applied in the past, which works well on this concept. 41 49 Although these models are very easy and simple to apply as it involves less computational work, their reliability and accuracy are debatable. 1 , 40 These indices suffer inaccuracies due to the absence of the incorporation of other factors like asphaltene and resins compositional and structural properties and operational conditions such as temperature and pressure conditions which are equally important for judging asphaltene stability in crude oils.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are various stability assessment methods proposed to determine the asphaltene deposition risk potential in crude oils. Among them, one of the methods is based on determining asphaltene stability in crude oil on the basis of crude oil SARA values. , The basic concept behind this method is that crude oil is found to be more risky in terms of asphaltene deposition if it contains higher contents of saturates and asphaltene and lower contents of resins and aromatic contents. , Different models like the colloidal instability index (CII), stability index (SI), colloidal stability index (CSI), Stankiewicz plot (SP), ANJIS Model, qualitative–quantitative analysis (QQA), and stability cross plot (SCP) were developed and applied in the past, which works well on this concept. Although these models are very easy and simple to apply as it involves less computational work, their reliability and accuracy are debatable. , These indices suffer inaccuracies due to the absence of the incorporation of other factors like asphaltene and resins compositional and structural properties and operational conditions such as temperature and pressure conditions which are equally important for judging asphaltene stability in crude oils . In addition, these parameters take SARA values as input which are determined through various techniques and found to have significant differences in values from each other; therefore, in this context it may produce different stability outcomes for same crude oil. ,,, Moreover, recent studies reported that these SARA-based parameters produce biased predictions, i.e., predict certain classes better, and because of this a significant difference is usually found in the prediction outcomes of these models. , The second way of determining asphaltene stability in crude oils is to use thermodynamic models .…”
Section: Introductionmentioning
confidence: 99%